2018
DOI: 10.1108/sbm-02-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Football clubs as mediators in sponsor-stakeholder relations

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…In his case study of top Swedish football club Malmø FF, Junghagen (2018) found that exposure had a lower-than-expected value for several sponsors. Exposure was not a target in the agreement for this sponsor group; what was valuable for this type of sponsor group involved the network itself.…”
Section: Value Of Network For Sponsors and Sponsor Objectsmentioning
confidence: 97%
See 3 more Smart Citations
“…In his case study of top Swedish football club Malmø FF, Junghagen (2018) found that exposure had a lower-than-expected value for several sponsors. Exposure was not a target in the agreement for this sponsor group; what was valuable for this type of sponsor group involved the network itself.…”
Section: Value Of Network For Sponsors and Sponsor Objectsmentioning
confidence: 97%
“…Exposure was not a target in the agreement for this sponsor group; what was valuable for this type of sponsor group involved the network itself. The recommendation for the owner of the sponsor network is to work with stakeholder management beyond the sponsor-club dyad (Junghagen, 2018). The arbitrator's role is, among other things, to visualise the network, lead the portfolio of sponsors, and set up an interaction between the sponsors (Cobbs, 2011;Ryan and Fahy, 2012).…”
Section: Value Of Network For Sponsors and Sponsor Objectsmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable amount of research has focused on sports brands, such as teams or clubs (Ara ujo, Pablo de Carlos and Fraiz, 2014;Gasparetto, Barajas and Fernandez-Jardon, 2018;Junghagen, 2018;Richelieu and Desbordes, 2013;Richelieu and Lessard, 2014), and on the retail branding strategies of professional football clubs (Szymoszowskyj, Winand, Kolyperas and Sparks, 2016). Little research has focused on the sporting goods brands used by registered amateur football players.…”
Section: Introductionmentioning
confidence: 99%